Lignin Nanoparticles as Antifungal Agent for Bamboo - Marshallanore, Amat; Chin, Suk Fun; Ngieng, Ngui Sing; Mohd Effendi, Wasli; Awang Ahmad Sallehin, Awang Husaini (UNIMAS Publisher, 2025)
Lignin is the most abundant aromatic polymer and the second most abundant biopolymer after cellulose. It is a complex biopolymer composed of different amounts of monolignols, namely p-coumaryl alcohol, coniferyl alcohol, and sinapyl alcohol (Ralph et al., 2019). Lignin can be used in industry because it is low-cost, non-toxic, biodegradable, and biocompatible.